2003
DOI: 10.1002/chin.200313209
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic: An Environmental Problem Limited by Solubility

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 1 publication
0
47
0
3
Order By: Relevance
“…The release of As from CaHAsO 4 is possible in an aerobic environment when CO 2 reacts with CaHAsO 4 , causing CaHAsO 4 to become unstable while CaCO 3 remains stable (Caille et al 2003;Magalhaes 2002). Krishnamurti and Naidu (2007) confirmed that when sediment pH exceeds 8, specific trace metals (Cu, Zn, and Cd) can be soluble.…”
Section: Aluminum Arsenic Barium and Coppermentioning
confidence: 73%
See 3 more Smart Citations
“…The release of As from CaHAsO 4 is possible in an aerobic environment when CO 2 reacts with CaHAsO 4 , causing CaHAsO 4 to become unstable while CaCO 3 remains stable (Caille et al 2003;Magalhaes 2002). Krishnamurti and Naidu (2007) confirmed that when sediment pH exceeds 8, specific trace metals (Cu, Zn, and Cd) can be soluble.…”
Section: Aluminum Arsenic Barium and Coppermentioning
confidence: 73%
“…Sediment found in many arid climates have a similar pH, as described above, including the Three Kids Mine, which ranges between 7.8 and 8.15. This high pH may possibly induce mobility of As and Pb, as described by Krishnamurti and Naidu (2007) and Magalhaes (2002). Other studies by Caille et al (2003) and Wong et al (1999) have also shown that some metalloids and trace metals are soluble in an aerobic environment where pH [ 8.0.…”
Section: Aluminum Arsenic Barium and Coppermentioning
confidence: 86%
See 2 more Smart Citations
“…Based on a sequential extraction developed for As and scanning electron microscopy/X-ray spectrophotometry results, the significance of Ca for As retention is suggested to be negligible even in calcareous soils, since As is primarily bound to Fe oxides [181,182]. Even if Ca-As compounds are formed in soil, dissolved As concentration in soil solution in equilibrium with calcium arsenates in the pH range of 4.5-8.5 might be too high to mitigate ecotoxicological risks [183].…”
Section: Liming Compoundsmentioning
confidence: 99%